Business valuation body of knowledge : - Pratt, Shannon P. (John Wiley & Sons, Inc., 2003)
The Business Valuation Body of Knowledge Workbook, Second Edition provides both a study guide for candidates preparing for ABV, ASA, CBA, or CVA certification and a training tool for practitioners conducting business valuations. To be used in conjunction with an in-house training program or simply for independent study and reference, the Workbook: Includes questions and exercises that typically appear on accreditation exams; Covers the most frequently encountered errors on reports and in examinations; Reflects the latest business valuation developments, viewpoints, court case references, and data resources; Contains hundreds of multiple-choice and true/false questions, short problems, and fill-in-the-blank questions; Includes eight hours of CPE credit through a self-study examination.